Implementasi Regulatory Sandbox dalam Konteks Pengawasan Pangan Olahan di Indonesia - Handoko, Yulian Dwi Anggraeni Puspa; Wibowo, Andi; Arrahman, Yovia Rizki; Fauziah, Pepi; Yuliani (Badan Pengawas Obat dan Makanan, 2024)
The enhancement of innovation in processed food products in Indonesia faces regulatory challenges that often limit the speed and flexibility of development, particularly for high-risk products. The recent implementation of the Omnibus Law has brought significant changes to the food oversight framework, including the exemption of criminal sanctions for low to medium-risk business activities and the transition of distribution permits into business licenses. However, these regulations have not fully addressed the barriers to innovation in processed food development. The concept of a regulatory sandbox has been identified as a promising prospective approach to overcoming these challenges, providing a controlled testing environment for businesses to develop innovative products within a more adaptive ecosystem. This article explores the potential of a regulatory sandbox as a creative tool for overseeing high-risk processed food products through a qualitative literature review method. The study indicates that the success of implementing a sandbox depends on several key factors: collecting robust experimental data to assess product safety and efficacy, developing adaptive procedures responsive to industry feedback, and granting limited yet flexible authorization for testing new technologies. Other factors, such as limitations on the duration, scope, and use of the sandbox, must be established to avoid consumer safety risks. As a recommendation, The Indonesian Food and Drug Authority (BPOM) may consider adopting a regulatory sandbox as a strategic framework to support the oversight of processed food products with a dynamic approach, accelerating innovation while maintaining a balance between consumer safety and industry growth.